2015
DOI: 10.1037/cfp0000045
|View full text |Cite
|
Sign up to set email alerts
|

Legal and social ceremonies to formalize same-sex relationships: Associations with commitment, social support, and relationship outcomes.

Abstract: In this study, we explored whether the formalization of same-sex relationships via legal or social ceremonies is associated with relationship outcomes, and whether these associations could be accounted for by enhanced commitment or social support for the relationship. At Time 1, a geographically diverse sample of 604 U.S. adults in cohabiting same-sex relationships reported on whether they had formalized their relationship through a legal or social commitment ceremony, commitment to the relationship, and relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…The most frequently assessed outcomes are global relationship quality (e.g., Balsam et al, 2008; Roisman et al, 2008) or relationship satisfaction (e.g., Boesch et al, 2007; Kamen et al, 2011; Kurdek, 2004). Longitudinal studies in this review often focused on relationship stability (Gottman, Levenson, Gross, et al, 2003; Rosenfeld, 2014; Whitton et al, 2015) or change in global relationship quality over time (Kurdek, 2008b). One longitudinal study examined life satisfaction and parenting alliance as outcomes (Tornello et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently assessed outcomes are global relationship quality (e.g., Balsam et al, 2008; Roisman et al, 2008) or relationship satisfaction (e.g., Boesch et al, 2007; Kamen et al, 2011; Kurdek, 2004). Longitudinal studies in this review often focused on relationship stability (Gottman, Levenson, Gross, et al, 2003; Rosenfeld, 2014; Whitton et al, 2015) or change in global relationship quality over time (Kurdek, 2008b). One longitudinal study examined life satisfaction and parenting alliance as outcomes (Tornello et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In a national sample of gay, lesbian, and bisexual individuals, participants who had some kind of legal relationship status (i.e., civil union, domestic partnership, civil marriage) reported more meaning in life, less internalized stigma, fewer depressive symptoms, and less stress than participants who were in committed relationships that did not have legal status (Riggle, Rostosky, & Horne, 2010a, 2010b). Legal recognition for one’s relationship has also been associated with relationship stability (Whitton, Kuryluk, & Khaddouma, 2015). In analysis of a nationally representative longitudinal survey, Rosenfeld (2014) found that being in a legally recognized relationship, or even simply considering yourself “married” without any formal status, reduced the odds of relationship dissolution for both same-sex and different-sex couples.…”
Section: Internal Strengths Of Same-sex Couple Relationshipsmentioning
confidence: 99%
“…Nonetheless, the growing cultural acceptance of same‐sex partnerships, reinforced by the legalization of same‐sex marriages, arguably strengthens commitment and stability in the form of long‐term and monogamous relationships, much like it does for different‐sex relationships (Joyner, Manning, & Bogle, ; Lau, ; Monk, Ogolsky, & Oswald, ). Variation in institutionalization of same‐sex marriage across countries suggests one important mechanism shaping both relationship formation processes and union stability (Joyner et al, ; Potârcă et al, ), given the research that legal formalization is associated with greater relationship stability (Whitton, Kuryluk, & Khaddouma, ). There are many challenges to studying same‐sex relationships (Reczek, ).…”
Section: Research Themesmentioning
confidence: 99%
“…Nowadays, pressure to legalise same-sex relationships is growing; this is related to the greater mutual commitment of the partners, but also to greater social support for such a relationship. Adult men and women who are in legalised same-sex relationships are found to be more satisfied and their relations are more stable than those from non-legalised relationships (Andersson et al, 2006;Julien et al, 2003;Kurdek, 2004;McLanahan & Beck, 2010;Solomon et al, 2008;Whitton et al, 2015). Lack of social acceptance and adequate legislation for same-sex relationships results in same-sex couples living together in secret, without any sense of long-term security or dependence concerning inter alia financial matters, inheritance rights or mutual care, which may weaken relations between the partners.…”
Section: Discussionmentioning
confidence: 99%